PERANAN KUALITAS PELAYANAN DALAM UPAYA MENINGKATKAN NASABAH PRODUK SIMPANAN PADA BANK-BANK BUMN DIKOTA BANJARMASIN - Rory Handriano (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, This study aims to determine the role of service quality in efforts to improve customers of BUMN bank savings in the city of Banjarmasin. The method used in this research is the method of observation, interviews, questionnaires, and literature study on services provided by state-owned banks in the city of Banjarmasin so that the expectations of customers to obtain the best service can be achieved. In this study, it was found that there is still a lack of confidence in some small and medium-sized communities towards banking products due to their lack of understanding of banking services and the existence of phobias in small and medium-sized communities in the banking sector that is notoriously tight and difficult.One effort that can be done so that state-owned banks in the city of Banjarmasin can maintain and continue to improve the quality of its services is to understand all the needs of customers and always provide regular / continuous training on providing excellent service (service excellence) to every employee, so that the quality of service can optimally upgraded to its customers.